2006
DOI: 10.1089/pho.2006.24.101
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation of Pain in Carpal Tunnel Syndrome: Review of Seven Laser Therapy Studies

Abstract: In this review, seven studies using photoradiation to treat carpal tunnel syndrome (CTS) are discussed: two controlled studies that observed real laser to have a better effect than sham laser, to treat CTS; three openprotocol studies that observed real laser to have a beneficial effect to treat CTS; and two studies that did not observe real laser to have a better effect than a control condition, to treat CTS. In the five studies that observed beneficial effect from real laser, higher laser dosages (9 Joules, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 29 publications
2
24
0
1
Order By: Relevance
“…The VAS of the moderate CTS patients was decreased to 3.76 ± 1.81. The results of our study were similar to the previous researches 3,5) and confirmed immediate pain alleviation of LLLT. We also found that LLLT could not maintain this effect for the next five weeks, and thus further research with longer follow-up periods were required.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The VAS of the moderate CTS patients was decreased to 3.76 ± 1.81. The results of our study were similar to the previous researches 3,5) and confirmed immediate pain alleviation of LLLT. We also found that LLLT could not maintain this effect for the next five weeks, and thus further research with longer follow-up periods were required.…”
Section: Discussionsupporting
confidence: 92%
“…The analgesic effect of LLLT is still controversial, but the clinical effect is confirmed 4,8) . 5,7,8,12) , and enhance the respiration metabolism of the cells 13) . Those metabolisms reduce the wastes from the inflammation including leukotrienes and metabolite which could improve the healing process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations